PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN HUMAN CAPITAL TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Ulfa Nur Haizah; Alfato Yusnar Kharismasyah; Suyoto Suyoto; Totok Haryanto (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: The development of modern organizations requires companies to have high-quality human resources, making leadership and human capital management increasingly important. This study aims to analyze the influence of transformational leadership and human capital on employee performance, with job satisfaction as a mediating variable. The model is designed to provide a more comprehensive understanding of how these factors work to enhance employee performance within the company.Methods: This research employed a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The respondents consisted of all employees, totaling 185 individuals selected using accidental sampling. Data were collected via a questionnaire that included indicators of transformational leadership, human capital, job satisfaction, and employee performance, measured on a 1–5 Likert scale.Results: The results showed that Human Capital and Job Satisfaction have a positive and significant effect on Employee Performance. Transformational Leadership has a positive but not significant effect on Employee Performance. Transformational Leadership and Human Capital have been proven to positively affect Job Satisfaction. Furthermore, Job Satisfaction is confirmed to mediate the positive influence of Transformational Leadership and Human Capital on Employee Performance. The research recommendations for the company indicate that although Transformational Leadership has not directly influenced Employee Performance, the company still needs to improve leadership quality by emphasizing motivation, support, and employee development. The company is also advised to strengthen Human Capital through continuous training and competency development programs to enhance Job Satisfaction and Employee Performance. These efforts are expected to create a more supportive work environment and improve Job Satisfaction and Employee Performance. In addition, the company should maintain a fair reward and compensation system, foster a conducive organizational climate, and encourage employee involvement in decision-making as part of a long-term performance improvement strategy. Keywords: Employee Performance, Human Capital, Job Satisfaction, Transformational Leadership